Products of enteropathogenic Escherichia coli inhibit lymphocyte activation and lymphokine production. - Klapproth, J M (1995)
The aim of this study was to determine whether products of enteric bacteria are able to regulate lymphocyte activation and cytokine production. Whole bacteria and bacterial lysates from different strains of Escherichia coli were tested for their ability to inhibit cytokine production by peripheral blood mononuclear cells as determined by reverse transcription-PCR, Northern (RNA) blotting of cellular RNA, or enzyme-linked immunosorbent assay for cytokine protein. Lysates from two pathogenic strains of E. coli, enteropathogenic E. coli (EPEC) and enterohemorrhagic E. coli, inhibited mitogen-stimulated expression of interleukin-2 (IL-2), IL-4, IL-5, and gamma interferon. IL-1 beta, IL-6, IL-8, IL-10, IL-12, and Rantes mRNA expression was not affected. The inhibitory activity was dose dependent, protease and heat sensitive, nondialyzable, and not due to cellular toxicity. The inhibitory activity remained in EPEC strains having mutations in known virulence factors. Nonpathogenic E. coli HB101 transformed with a 22-kb cosmid clone derived from EPEC chromosomal DNA expressed the inhibitory activity. Thus, certain strains of pathogenic E. coli express a protein or proteins encoded by chromosomal genes that selectively inhibit lymphocyte activation and lymphokine production. Therefore, immunosuppressive factors produced by pathogenic bacteria could be important in modifying gastrointestinal immune responses in enteric bacterial infections or gastrointestinal autoimmune diseases.